Cerebral hypoxia during immediate transition after birth and short term neurological outcome. (July 2017) - Pansy, Jasmin; Baik, Nariae; Schwaberger, Bernhard; Scheuchenegger, Anna; Pichler-Stachl, Elisabeth; Avian, Alexander; Schmölzer, Georg M.; Urlesberger, Berndt; Pichler, Gerhard
Abstract: In preterm neonates we investigated cerebral hypoxia assessed with near-infrared-spectroscopy during immediate transition after birth and general movement optimality score assessed before discharge. General movement optimality score decreased with increasing cerebral hypoxia. Burden of cerebral hypoxia during immediate transition might be associated with impaired short-term neurological outcome in preterm neonates. Highlights: General movement assessment (GMA) is a reliable tool for early detection of neurodevelopmental disability in early infancy. The general movement optimality score (GMOS) enables a more differentiated analysis compared to the less specific GMA. Preterms with a high burden of cerebral hypoxia during transition have a lower GMOS, indicating a worse neurological outcome.